Vitamin D levels on sports injuries in outdoor and indoor athletes: a cross-sectional study - Senisik, S.; Köyagasioglu, O.; Denerel, N. (The Physician and Sportsmedicine, 2022)
Objective Having vitamin D levels within normal limits is important for bone and muscle health and its deficiency may increase the risk of injury. The aim of this cross-sectional study was to investigate whether vitamin D levels are different in indoor and outdoor athletes and its levels increase the risk of injury.